Kajian Dalam Perspektif Filsafat Hukum Pada Implementasi Penerapan Diversi: Terhadap Penyelesaian Tindak Pidana Anak Di Tingkat Penuntutan - Ferdy Ardhany Ferdy; Herwin Sulistyowati Herwin (Justicia Journal, 2024)
The philosophy of law is a part of the search that is studied in the sphere of philosophical scope. Philosophy is a systematic thinking activity that can only be satisfied with accepting the results arising from the thinking activity itself. Philosophy does not limit itself only to sensory, physical, psychological or spiritual symptoms. He also asks not only "why" and "how" these symptoms are, but also the basis of the symptoms, their characteristics and their truth. He tries to reflect the theoretical relationship in which the symptoms are understood or thought out. In that case, the philosopher will never be satisfied with an answer. Every argument must be reasoned or made and understood rationally. Because however philosophy is an activity of thinking meaning in a dialogical relationship with the others he tries to formulate arguments to obtain examination. Next, philosophy is in fact open and tolerant. Philosophy is not a belief or a dogmatism, if it is no longer open to new arguments and firmly adheres to the understanding once acquired, it is not surprising that philosophy practically leads to rigidity. As a philosophy, the philosophers of law should have an attitude of adaptation to the nature, methods and purposes of philosophies in general. Furthermore, the law as the object of the philosophy of law will influence the philology of law. The future of the child becomes our responsibility together except for the child who is faced with the law. The protection of children who are facing the law one of them is Diversi at every stage of law enforcement both in the investigation, prosecution, and examination in the Court. Therefore, in order for the diversi effort can be implemented optimally and be the best alternative in the settlement of criminal cases of children, there is a need for improvement in the Law No. 11 of 2012 on the Child Criminal Justice System, given the obligation of the law-enforcement authorities to implement Diversi it is good to counter with the obligations of the parties in following Diversi; there is need for deeper socialization by the law enforce about what is diversi, what is Restorative Justice so that the wider public will understand the importance of Diversi as an effort to protect children who face the Law. The concept of law as the main objective of the philosophical struggle is as old as the history of philosophy itself. From ancient Greece to later times, the law was always discussed and questioned, that is, about its existence and reality. For the person who desires to know the law in depth, then he should strive to talk about the truth and origin of the law, the relationship of law with the Reflection and the Relevance of the Thought of the Philosophy of Law.